Graceful leadership in early childhood education - Terrell, Ann McClain (Redleaf Press, 2018)
"Graceful Leadership in Early Childhood Education" shares how the author maintained her signature graceful approach to being a more capable and effective leader in the field of early childhood. A great resource to turn to when there is a challenge that needs tackling, or if you just need to reflect on your own journey"--